Por uma cartografia escolar interativa: jogo digital para a alfabetização cartográfica no ensino fundamental - Dambros, Gabriela (2014)
The Geography school needs to appropriate didactic resources and consonants methodologies with the contemporary, integrating the information technologies and communication to the educational process. This way, this present research has the general objective to contribute to the practice of school cartography via insertion of information technologies and communication. The specific objectives were: (a) to elaborate a digital game to support the teaching and learning of literacy cartographic; (b) to validate the game with the students of sixth graders of elementary school; (c) analyze the educational potential, the limits and possibilities of games embedded in the pedagogical practice of Geography. The research was conducted by means of a qualitative approach, type case study and, for the development of digital game, followed four stages: conception, planning, implementation and evaluation. The research validation was carried out with students of the sixth grade of elementary school of School State Professor Firmino Cardoso Junior, located in the urban area in the municipality of São Pedro do Sul/RS. Of the results, stands out the digital game elaborate which is entitled "Pedrinho e Pedrita knowing the map" and the website created to make it available and direct students and teachers to others sites that may enhance the pedagogical practice. It found that the didactic resource developed, enhances the learning of the basics of cartographic literacy and arouses the interest, motivating students from the interactivity afforded.